(untitled) - Kraynak, Cecie (Hoboken, NJ, 2006)
This book is your opportunity to prove to yourself that you've mastered Spanish verbs and can use them in a sentence. With Spanish Verbs For Dummies, Student edition, a little practice reading conjugation charts, and a pencil or pen, you're well-prepared to tackle even thhe most irregular verbs in the Spanish language.
Keywords: Ngôn ngữ Tây Ban Nha,Ngôn ngữ Tây Ban Nha,Spanish language,Spanish language; Động từ,Sách giáo khoa cho người nói tiếng nước ngoài,Tiếng Anh,Verb,English